2009
DOI: 10.1017/s1047951109990874
|View full text |Cite
|
Sign up to set email alerts
|

Aortic distensibility and dilation in Turner’s syndrome

Abstract: Individuals with Turner's syndrome, even without cardiovascular risk factors, do develop aortic dilation accompanied by decreased aortic distensibility, suggestive of an intrinsic abnormality in elastic property of the ascending aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 17 publications
(41 reference statements)
1
18
0
1
Order By: Relevance
“…The natural history of aortic dilatation remains unknown in patients with TS. An intrinsic abnormality of elasticity in the ascending aorta has been suggested (23), involving disruption of the transforming growth factor b pathway (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The natural history of aortic dilatation remains unknown in patients with TS. An intrinsic abnormality of elasticity in the ascending aorta has been suggested (23), involving disruption of the transforming growth factor b pathway (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Aortic dissection can be a fatal complication during pregnancy in TS (20 -23, 25, 26). Recent studies have shown that aortic dissection in TS women is related not only to aortic valve disease and coarctation but also to aortopathy similar to that in Marfan syndrome with a collagen defect or cystic medial degeneration without macrovascular defects (35)(36)(37)(38). From a national survey and a literature review in the United States, Karnis and co-workers (25) estimated that the maternal risk of death from rupture or dissection of the aorta in pregnancy may be as high as 2% in TS.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic dilation in those without risk factors was accompanied by decreased aortic distensibility, suggesting an intrinsic abnormality in elastic property of the ascending aorta. Individuals with aortic dimensions in excess of the 95th percentile with decreased distensibility should be followed closely, both clinically and echocardiographically (84). One study demonstrated that CoA stenting is a safe and effective procedure at midterm follow-up in a small cohort of patients with TS.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…The fact that death due to aortic dissection occurs in many younger TS women who have symptoms for O24 h before they seek medical attention emphasises the need to increase awareness of the critical significance of chest pain in young TS women (83). Aortic dissection can occur in TS without cardiac malformations or hypertension (83,84). Hypertension affects almost half of young adults with TS, and should therefore be closely monitored and treated vigorously (2).…”
Section: Cardiovascular Abnormalities In Transitionmentioning
confidence: 99%